Degree of external restraint of wall segments in semi‐massive reinforced concrete tanks: Part I rectangular segments. (28th September 2017) - Zych, Mariusz
Abstract : This paper presents graphs and formulas serving to define the distribution of the restraint degree of wall segments in rectangular reinforced concrete tanks. The most frequent cases occurring in engineering practice are analyzed, that is, wall segments erected during the first concreting stage and those restrained along three edges. For the latter ones, this paper defines the influence of vertical stiffness in construction joints (depending on the reinforcement degree) on the distribution of the restraint degree. This paper shows a substantial impact of the temperature profile (i.e., imposed strain resulting from the development of hydration heat) on the area where cracks occur first, and on the value and distribution of tensile stresses. A practical aspect of the analysis performed is the possibility of defining the restraint degree for cases and assumptions not included in EN 1992–3.